Nitrogen supply method affects growth, yield and must composition of young grape vines (Vitis vinifera L. cv Alicante Bouschet) in southern Brazil - Stefanello, Lincon Oliveira; Schwalbert, Raissa; Schwalbert, Rai Augusto; De Conti, Lessandro; Souza Kulmann, Matheus Severo de; Garlet, Luana Paula; Rippel Silveira, Marcia Liliane; Sautter, Claudia Kaehler; Bastos de Melo, George Wellington; Rozane, Danilo Eduardo [UNESP]; Brunetto, Gustavo (Elsevier B.V., 2020)
The aim of this study was to evaluate yield and chemical composition of the must in grapevines subjected to Nitrogen (N) supply methods in sandy soils. The vineyard cultivar was 'Alicante Bouschet' (Vitis vinifera L.) grafted on 1103 Paulsen rootstock, in southern Brazil. The treatments consisted of the application of 20 + 20 kg N ha(-1) without irrigation (NW), 20 + 20 kg N ha(-1) followed by irrigation (NFI), 20 + 20 kg N ha(-1) via fertigation (NF), 20 kg N ha(-1) via fertigation (1/2NF), and a control (C) without N application. The study was conducted during four crop seasons. Leaves were collected at flowering and veraison to determination N concentration. Stem diameter, grape yield and its components were determined. In the must were evaluated the total soluble solids (TSS), pH, total titratable acidity (TTA) and total anthocyanins (TA). The concentration of nitrate and ammonium in soil solution was determined. N application followed by irrigation or N supplied via fertigation provided to the vines larger stem diameters and leaf N concentrations, in most crop seasons. Grapevines submitted to N application via fertigation or followed by irrigation presented higher yields than conventional application without irrigation, and between two and three times higher than the control. N supply methods little affected total soluble solids contents. The application of N to the soil, regardless of the N supply method, decreased the anthocyanin concentration in the grape must, due to the dilution effect on the pulp/skin ratio, promoted by the yield increase.
Keywords: Nitrogen fertilization; Nitrogen fertigation; Leaf N concentration; Anthocyanins; Field study; Long-term